Implementation od PSAK 19 Zakat, infaq and Shadaqah Accounting in the Badan Amil Zakat Nasional (BAZNAS) Pontianak - Redhea, Yaswinta Ulfa (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
This study aims to analyze the application of zakat accounting based on PSAK 109 at the BAZNAS Pontianak. The approach used is researcher use a qualitative method descriptive analysis. The result showed that (1) The accounting process at the BAZNAS Pontianak was not fully in accordance with general accounting theory; (2) Recognition and measurement of zakat on BAZNAS Pontianak was in accordance with PSAK 109; and (3) Presentation and disclosure on BAZNAS Pontianak was not in accordance with PSAK 109.